2001
DOI: 10.1248/bpb.24.197
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Small Heat Shock Protein 27 (HSP27) in Mouse Skin Tumors Induced by UVB-Irradiation.

Abstract: We investigated the expression of heat shock protein 27 (HSP27) at intermediate stages of a cutaneous tumor induced by UVB-irradiation stress (290-380 nm, max. 312 nm) using an immunostaining method. After 15-20 weeks of chronic exposure to UVB irradiation at a dose of 2 kJ/m2, HSP27 was found in the upper cell layers of bowenoid multilayers of epidermis, in areas of the lesions where normal stratification seems to be conserved. After 25 weeks, HSP27 was weakly expressed in squamous cell carcinoma (SCC). The H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…The data obtained from these studies indicate that Hsp27 expression is strictly correlated to keratinocyte differentiation, suggesting that the absence of this protein in epidermal cells could be regarded as a marker of epidermal malignancy in all the species so far investigated (Trautinger et al 1995;Kiriyama et al 2001;Romanucci et al 2005). As a matter of fact, canine Hsp27 is also very similar to the human form with its primary structure deduced from nucleotide sequence revealing a 209 amino acid protein sharing 86-89% homology with human, mouse, rat and hamster small Hsp (Larsen et al 1995).…”
Section: Introductionmentioning
confidence: 96%
“…The data obtained from these studies indicate that Hsp27 expression is strictly correlated to keratinocyte differentiation, suggesting that the absence of this protein in epidermal cells could be regarded as a marker of epidermal malignancy in all the species so far investigated (Trautinger et al 1995;Kiriyama et al 2001;Romanucci et al 2005). As a matter of fact, canine Hsp27 is also very similar to the human form with its primary structure deduced from nucleotide sequence revealing a 209 amino acid protein sharing 86-89% homology with human, mouse, rat and hamster small Hsp (Larsen et al 1995).…”
Section: Introductionmentioning
confidence: 96%
“…However, little is known about the molecular mechanism regulating the conversion of cellular conditions such as proliferation, differentiation or cell death. In recent studies a family of heat shock proteins (HSP) has been suggested to regulate or switch the proliferation vs. differentiation or the proliferation vs. cell death [17, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…The 27-kD HSP (HSP27, small heat shock protein was originally named as HSP25 in mice; in this manuscript the molecule will be termed HSP27) form large oligomers that can act as molecular chaperones and can protect cells from heat shock and oxidative stress in vitro . Also, expression of HSP27 is reduced or absent in basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and other malignancies arising from keratinocytes, suggesting that the lack of HSP27 might be a marker of epidermal malignancy (7, 8). Another relevant HSP family is the 70-kD family.…”
Section: Introductionmentioning
confidence: 99%